Standardizing Darija: Collaborative approaches in the Moroccan Darija Wikipedia - Sedrati, Anass; Afifi, Mounir; Benkhadra, Reda (Lingua Posnaniensis, 2026)
This paper examines the development of Moroccan Darija Wikipedia since its launch in July 2020. It details the strategies employed by the Wikimedia Morocco user group, focusing on bot automation and editing contests, to foster growth within this low-resource language Wikipedia. The paper highlights the opportunities Darija Wikipedia presents for Artificial Intelligence research, particularly in Natural Language Processing, given its status as the largest online Darija dataset. It also explores how the standardization efforts undertaken by the user group enable valuable collaboration between volunteers, experts, and researchers, potentially setting a prece-dent for other similar language communities. Furthermore, the paper addresses key challenges, including ensuring community sustainability and mitigating vandalism, and analyzes the manifestation of diverse spelling conventions (phonetic, etymological) within the encyclopedia’s content.